Occurrence of lice infestation in Iraqi local buffaloes in Mosul city (NTU Journal of Agriculture and Veterinary Science, 2025)
The study aimed to evaluate epidemiological data risk factors such as seasons, sex, age, breed, area of study and feeding system. This study was applied during the months from January-2022 until December-2022. The Total numbers for examined buffaloes 1060 of buffaloes. The total infestation rate was 54.06%.Clinical gross examination results of skin of buffaloes revealed the presence of lice and eggs  with damaged hair and hair fall spots due to heavy infestation. Microscopical examination with dissecting microscope the local Iraqi buffaloes raised indoor are infested with sucking lice species Haematopinus tuberculatus, morphological identification of lice identify the species of lice in buffaloes  is the sucking lice Haematopinus tuberculatus according to the following morphological features;  adults are black to brown in colours, 3.8mm in long and 1.9mm wide without eyes. The paratergal plates were very prominent, antennae containing five segments and pointed head with one large claw in each leg.A total infestation rate (573/1060) 54.06%. Highest infestation rate was 79% in January, February March at p? 0.05. As for age risk factor the study results recorded 64.09% in animals more than three years compared with 37.5% for animals less than three years at p? 0.05 differences were significant. The highest infestation rate was 61.09% in female group compared with 43.09% in male. Location of study in revealed that infestation rate was the highest inside Hawy Al-Maslagh (right side) with 80% while the lowest was in Hammam Al-Alil (Tomb of the slave) with 36%.